Social entrepreneurship in youth culture: Morganics, Russell Simmons and Emile 'XY?' Jansen - Lombard, Kara-Jane (Taylor and Francis, 2012)
This article utilizes the concept of social entrepreneurship to explore one aspect of the increasing incorporation of youth cultures into the mainstream, in which youth culture participants undertake private and public sector roles simultaneously. The concept of social entrepreneurship is useful in understanding the mainstreaming of youth culture, suggesting that it does not just have value as a form of resistive expression, but can be harnessed by practitioners for both profit and socially progressive ends. Taking the subculture of hip hop as a case study, three contexts are explored — Morganics in Australia, “Russell Simmons: Philanthropist” in the USA and Emile “XY?” Jansen of the South African hip hop crew Black Noise. This investigation reveals how the concept of social entrepreneurship is inflected in local contexts, examining key differences around assets, funding, the role of government, the type of social entrepreneurship and the conditions under which it operates.